Implementasi Manajemen Kurikulum Di Sekolah Dasar - Salma Nur Fatihah; Sri Marmoah (Universitas Batanghari Jambi, 2026)
This study aims to describe the implementation of the Independent Curriculum management in elementary schools and analyze its supporting and inhibiting factors, focusing on learning planning, implementation, and evaluation. The study used a qualitative descriptive approach, with data collection techniques including interviews with principals and teachers, observations of learning activities, and analysis of documents such as learning outcomes, teaching modules, and school programs. The results show that curriculum planning is carried out through the development of contextual and differentiated teaching modules according to student characteristics. Learning implementation emphasizes project-based learning to strengthen the Pancasila Student Profile, the application of active learning strategies, and the use of digital media as support. Evaluation is carried out continuously through formative and summative assessments, accompanied by teacher reflection for continuous improvement. The discussion reveals that the successful implementation of the Independent Curriculum is influenced by teacher competence, principal support, parental participation, and the availability of infrastructure. However, obstacles still exist in the form of limited time for teachers to develop teaching modules and adapt to diagnostic assessments. The study's conclusions emphasize the importance of planned, collaborative, and student-needs-based curriculum management for optimal implementation of the Independent Curriculum. Recommendations focus on improving teacher training, utilizing educational technology, and strengthening school-stakeholder collaboration.